Pengembangan Alat Pelontar Shuttlecock sebagai Alat Latihan Netting - Pamungkas Nur Hidayat; Bimo Alexander; Andri Arif Kustiawan; Agus Pribadi (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to develop an economical shuttlecock launcher for badminton netting practice. The method used is Research and Development (R&D) with the ADDIE model. Subjects included one expert , 10 students (small-group trial), and 20 athletes from PB Diamond (large-group trial). Data were collected via Likert-scale questionnaires and analyzed using descriptive percentages. The results showed that the device, made of hollow iron and a 12-Volt DC motor, was assembled for Rp1,750,000. In the small-group trial, it scored 416 (83.2%), categorized as "Good". However, in the large-group trial, the score dropped to 768 (76.8%), falling into the "Cukup" (Fair) category. This decline was caused by technical limitations under high-intensity use , such as heat accumulation in the DC motor , a static trajectory , and shuttlecocks jamming in the storage tube. In conclusion, this innovative launcher is feasible for small-scale training , but requires further development, including cooling fans, automatic rotation mechanisms, and tube improvements for mass training.